Identification and characterisation of gut proteases in the fig tree skeletoniser moth, Choreutis nemorana Hübner (Lepidoptera: Choreutidae) - Moloud GHOLAMZADEH CHITGAR; Mohammad GHADAMYARI; Mahbobe SHARIFI (Plant Protection Science, 2013)
The biochemical properties of proteases from the digestive system of the fig tree skeletonizer moth, Choreutis nemorana, were determined. Gut extracts of C. nemorana larvae were analysed using different specific peptide substrates and proteinase inhibitors. The optimal pH and temperature for proteolytic activities using azocasein as substrate were obtained as pH 11 and 45°C, respectively. In the case of N-benzoyl-l-arg-p-nitroanilide as substrate, the enzyme showed the maximum tryptic activity at pH 11. The kinetic parameters of trypsin-like proteases indicated that the Km and Vmax values of trypsin in the gut of C. nemorana were 0.157 ± 0.006mM and 0.188 ± 0.005 µmol/min/mgprotein. Using specific proteolytic inhibitors, the inhibitors including phenyl methane sulfonyl fluoride, N-p-tosyl-l-lys chloromethyl ketone and ethylene diamine tetraacetic acid showed the greatest inhibitory effect on total proteolytic activity. These results indicated that serine proteinases accounted for the major proteases in the gut of C. nemorana. Inhibition assays and zymogram analysis showed that only small amounts of cysteine proteases are present in the digestive system of C. nemorana.